2018
DOI: 10.1542/peds.2018-0516j
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural Interactions and Shared Decision-making

Abstract: none of which were for talks on shared decision-making; and Dr Johnson has indicated she has no financial relationships relevant to this article to disclose.Shared decision-making (SDM) depends on high-quality communication between the physician and the decision maker. The shared beliefs, values, behaviors, and traditions that make up an individual's culture affect the way he or she communicates and receives information and impacts complex decision-making. Cultural differences between medical providers and pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…A qualitative study conducted to analyse the perspectives of US paediatricians regarding shared decision-making in ADHD showed that instead of familiarizing families with all the options first, the paediatricians provided information to persuade families to accept the treatment of their choice [ 70 ]. These different scenarios can be explained in part by the quality of communication between the physician and the patient/parent, the technical language used, and possibly the cultural context of both parties [ 71 ] as well as the development of medical bioethics and doctor–patient communication skills [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study conducted to analyse the perspectives of US paediatricians regarding shared decision-making in ADHD showed that instead of familiarizing families with all the options first, the paediatricians provided information to persuade families to accept the treatment of their choice [ 70 ]. These different scenarios can be explained in part by the quality of communication between the physician and the patient/parent, the technical language used, and possibly the cultural context of both parties [ 71 ] as well as the development of medical bioethics and doctor–patient communication skills [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study conducted to analyse the perspectives of U.S. paediatricians regarding shared decision-making in ADHD indicated that instead of familiarizing families with all the options rst, the paediatricians provided information to persuade families to accept the treatment of their choice [73]. These different scenarios can be explained in part by the quality of communication between the physician and the patient/parent, the technical language used and possibly the cultural context of both parties [74] as well as the development of medical bioethics and doctor-patient communication skills [75].…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study conducted to analyse the perspectives of US paediatricians regarding shared decision-making in ADHD indicated that instead of familiarizing families with all the options rst, the paediatricians provided information to persuade families to accept the treatment of their choice [70]. These different scenarios can be explained in part by the quality of communication between the physician and the patient/parent, the technical language used and possibly the cultural context of both parties [71] as well as the development of medical bioethics and doctor-patient communication skills [72].…”
Section: Discussionmentioning
confidence: 99%